2018
DOI: 10.1073/pnas.1703643115
|View full text |Cite
|
Sign up to set email alerts
|

Brain-to-brain coupling during handholding is associated with pain reduction

Abstract: The mechanisms underlying analgesia related to social touch are not clear. While recent research highlights the role of the empathy of the observer to pain relief in the target, the contribution of social interaction to analgesia is unknown. The current study examines brain-to-brain coupling during pain with interpersonal touch and tests the involvement of interbrain synchrony in pain alleviation. Romantic partners were assigned the roles of target (pain receiver) and observer (pain observer) under pain-no-pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
194
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 243 publications
(232 citation statements)
references
References 129 publications
10
194
0
3
Order By: Relevance
“…During the positive movie zygomatic synchrony significantly co-varied with cardiovascular synchrony as both manifested convergence in positive feelings. This finding is in line with previous research linking synchronous physiological processes in interacting individuals with shared emotional experiences, such as emotional contagion and empathy 3,7,68,69 . In contrast, during the negative movie, zygomatic synchrony didn't show such association with cardiovascular synchrony or with emotional convergence, suggesting that it played a different functional role.…”
Section: Association With Affiliative Feelingssupporting
confidence: 92%
See 1 more Smart Citation
“…During the positive movie zygomatic synchrony significantly co-varied with cardiovascular synchrony as both manifested convergence in positive feelings. This finding is in line with previous research linking synchronous physiological processes in interacting individuals with shared emotional experiences, such as emotional contagion and empathy 3,7,68,69 . In contrast, during the negative movie, zygomatic synchrony didn't show such association with cardiovascular synchrony or with emotional convergence, suggesting that it played a different functional role.…”
Section: Association With Affiliative Feelingssupporting
confidence: 92%
“…Given its central role in human flourishing and wellbeing 2 , it is important to understand the biologically-wired mechanisms which allow people to rapidly and effortlessly form social bonds. It has been suggested that one such mechanism is interpersonal synchrony -the pervasive tendency of individuals to become coupled or synchronized with each other during interaction [3][4][5][6][7][8] . Past research has indeed suggested that interpersonal alignment of neural responses between interacting individuals binds them into a social unit, promoting mutual emotional and social states 3,[6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, social touch between romantic partners during the experience of pain strengthens inter-partner brain-to-brain coupling in the alpha/mu-band, and this brain-to-brain coupling enhances touchrelated analgesia and empathic accuracy (Goldstein, Weissman-Fogel, Dumas, & Shamay-Tsoory, 2018). Given that intranasal OXT augments alpha-band inter-brain neural oscillations during a social coordination task (Mu, Guo, & Han, 2016), we hypothesize that OXT also modulates brain-to-brain coupling between romantic partners.…”
Section: Discussionmentioning
confidence: 94%
“…A central question for future work is how this synchrony arises in the brain and how it interacts with neural systems known to be involved in threat learning. It might be possible to use hyperscanning techniques in humans using EEG or fMRI [36,56], to address this question using the experimental paradigm established here. Another promising method would be to begin with investigating if similar synchrony can be found in rodent models, where neural recordings of sub-cortical structures implicated in arousal are more readily available.…”
Section: Discussionmentioning
confidence: 99%